2021
DOI: 10.3389/fonc.2021.658552
|View full text |Cite|
|
Sign up to set email alerts
|

Chemoresistance and Metastasis in Breast Cancer Molecular Mechanisms and Novel Clinical Strategies

Abstract: Breast cancer is the most common malignant tumor in females worldwide. Chemotherapy is the standard breast cancer treatment; however, chemoresistance is often seen in patients with metastatic breast cancer. Owing to high heterogeneity, the mechanisms of breast cancer chemoresistance and metastasis have not been fully investigated. The possible molecular mechanisms of chemoresistance in breast cancer include efflux transporters, signaling pathways, non-coding RNAs, and cancer stem cells. However, to overcome th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 108 publications
(134 reference statements)
0
31
0
Order By: Relevance
“…Medication has a low clinical benefit in TNBC patients, therefore, finding molecular targets for TNBC treatment is essential for acquiring appropriate therapeutic targets. Several pathways can be targeted, including BRCA, Wnt/β-catenin, NF-κB, Hedgehog, JAK, PD-1/PD-L1, PI3K/Akt/m-TOR, EGFR [230,231], and others that have long been part of the treatment strategy. Finding new and effective treatment options for TNBC remains a critical clinical need.…”
Section: Future and Prospectsmentioning
confidence: 99%
“…Medication has a low clinical benefit in TNBC patients, therefore, finding molecular targets for TNBC treatment is essential for acquiring appropriate therapeutic targets. Several pathways can be targeted, including BRCA, Wnt/β-catenin, NF-κB, Hedgehog, JAK, PD-1/PD-L1, PI3K/Akt/m-TOR, EGFR [230,231], and others that have long been part of the treatment strategy. Finding new and effective treatment options for TNBC remains a critical clinical need.…”
Section: Future and Prospectsmentioning
confidence: 99%
“…As in other solid tumors, several studies reported a regulatory role for different miRNAs [ 84 , 85 ], and some miRNA expression profiles are associated with resistance to chemotherapy in breast tumors [ 86 , 87 ]. Zhou et al revealed that MCF7 breast cancer cells resistant to Adriamycin have significant over-expression of miR-29b-3p and miR-29b1-5p [ 88 ].…”
Section: Roles Of Mir-29b In Breast Cancermentioning
confidence: 99%
“…The advancement on knowledge of breast cancer and the use of personalized medicine, have greatly improved the prognosis and survival rates compared to previous decades [54]. However, as already mentioned, breast cancer continues to be the leading cause of cancer mortality in women, with 685,000 deaths only in 2020 [2], prompting researchers to conduct research on new treatments, especially for the advanced stages, presence of metastasis or cancer types with a poorer prognosis due to chemoresistance, such as triple-negative [55,56].…”
Section: Treatments and Prognosismentioning
confidence: 99%